Epidemiology of occupational health - Karvonen, M.; Mikheev, Mikhail; World Health Organization. Regional Office for Europe (Copenhagen : WHO Regional Office for Europe, 1986)
A collection of articles focused on the ways that epidemiological methods can be used to improve knowledge of the health hazards associated with different occupations or risks at the workplace. The objective is to point out any special problems that must be considered when applying established epidemiological methods to the field of occupational health. Specific applications covered in the book include the identification of occupational health risks, the evaluation of long-term effects, the selection of reliable sources of data, and the use of screening in the assessment of risks. Other chapters discuss methods and procedures in descriptive epidemiology, cross-sectional studies, cohort studies, case-control studies, and studies of combined effects.
Russian version of nos. 16-24 bound together (barcode no. 00073858).
chi eng rus.
vie
WHODOC
WHO monograph
4
Keywords: Occupational diseases; Epidemiology